Evaluation of the Effects of Citrus paradisi (Rutaceae) Fruit Juice on Electrolyte, Hepatic, Haematological and Histological Derangements in Streptozotocin-Induced Diabetic rats. - Stephen, Ekperikpe Ubong; Josephine, Owolabi Omonkhelin; Olapeju, Bolanle Israel (Nigerian Journal of Pharmaceutical and Applied Science Research, 2019)
This study investigated the effects of Citrus paradisi fruit juice on biochemical, haematological and histopathological indices in streptozotocin-induced diabetic rats. Wistar rats of either sex (180-300 g) were fasted overnight and diabetes mellitus induced using streptozotocin 40 mg/kg IP. Diabetes mellitus (fasting blood glucose ? 200 mg/dl) was confirmed 48 hours later. The rats were randomly grouped into six (n = 5). Fourteen days later, the rats were sacrificed under chloroform anaesthesia. Vital organs (kidneys, liver and pancreas) and blood samples were obtained for histopathological, biochemical and haematological analysis. Citrus paradisi (500 mg/kg and 1000 mg/kg) caused significant (p < 0.05) elevations in red blood cell counts and red blood cell indices. Citrus paradisi (250 mg/kg, 500 mg/kg and 1000 mg/kg) caused significant (p < 0.05) reductions in white blood cell and platelet counts but did not significantly affect the differential white blood cell count. Liver transaminases and total bilirubin were reduced significantly (p < 0.05) while the total protein was significantly increased (p < 0.05). Citrus paradisi (500 mg/kg and 1000 mg/kg) brought about significant improvements in the histopathological indices in diabetic rats. These data suggest that Citrus paradisi ameliorates biochemical, haematological and histopathological changes associates with diabetes mellitus.